Impact of a home-based cardiac rehabilitation program in heart failure during the COVID-19 pandemic. (11th May 2022) - Schmidt, C; Basilio, PG; Magalhaes, S; Alexandre, A; Barreira, A; Fernandes, P; Ribeiro, F; Santos, M
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): This work was financially supported by the project POCI-01-0145-FEDER-030011, funded by FEDER, through COMPETE2020-POCI, and by national funds, through FCT/MCTES (PTDC/MEC-CAR/30011/2017). CIAFEL, UnIC and UMIB are supported by national funds through Fundação para a Ciência e Tecnologia, I.P. [(UIDB/00617/2020), (UIDB/00051/2020 and UIDP/00051/2020), and (UIDB/00215/2020 and UIDP/00215/2020), respectively]. CS received an individual grant from CAPES [BEX 0554/14-6]. Introduction: Cardiac rehabilitation (CR) is an evidence-based recommended treatment of heart failure (HF) patients. During the COVID-19 pandemic, the shutdown of CR centers was necessary to limit the infection risk among high-risk patients. The integration of a home-based CR (HBCR) program in CR units can help to improve the delivery of care and improve cardiovascular outcomes of HF patients. Purpose: To assess the effectiveness of an HBCR program in HF patients. Methods: This is a substudy of the EXercise InTervention in Heart Failure trial (EXIT-HF), which include forty-nine HF patients (preserved and reduced ejection fraction). The HBCR program consisted in 12-week combined exercise program (60%-80% of peak oxygen consumption (VO2 peak)), 2 training sessions per week, for a total of 24 sessions. Patients performed 4 supervised training sessions and the remaining sessions at home. All patients performed a cardiopulmonary exercise test (VO2 peak), the 6-minute-walking test (6MWT), collected blood analysis (plasma NT-proBNP), and answered the Minnesota Living with Heart Failure Questionnaire. Results: Forty-two patients (86%) complete at least 80% of prescribed training sessions (age: 61.1±12; FEVE: 37.1±10.8). The HBCR program improve VO2 peak from 18.3 to 20.1ml/kg/min (+1.8 ml/kg/min; 95%IC:1.4 to 2.4; p<0.001) and the walked distance at the 6MWT from 462 to 512 meters (+49 meters; 95%IC: 38 to 60; p<0.001). In addition, overall quality of life was improved (-13 points; 95%IC:-7.8 to -18.5; p<0.001), as well physical (-6.3 points; 95%IC:-3.5 to -9; p<0.001) and emotional dimension of quality of life (-2.8points ; 95%IC: -0.9 to -4.7; p=0.06). No significant change was found in NT-proBNP levels (820±1220 vs 674±903; p=0.285). Conclusions: Our results showed that HBCR is feasible and can improve functional capacity and quality of life in HF patients.